Autocorrelation and heteroskedasticity in equations describing the demand for money during rapid inflations - Jaksch, Hans Jürgen (Empirical economics, 1993)
Estimating econometric equations with linear autoregressive error terms is standard if the covariance matrix of these error terms are homoskedastic. However, if heteroskedasticity prevails, this heteroskedasticity should be taken into account in order to obtain efficient estimates. In this paper, the well-known maximum-likelihood estimation method due to Beach and MacKinnon (1978) is extended to the heteroskedastic case and then applied to equations describing the demand for money in advanced inflations. Since this method isnot a straightforward generalization of the Beach-MacKinnon procedure, it not necessarily leads to estimates which are to be preferred to those obtained under the assumption of homoskedasticity.
Gesehen am 23.08.2024
Keywords: 1920-1923; 1977-1987; Argentinien